2022
DOI: 10.2147/opth.s375587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylactic Mitomycin C on Corneal Endothelium Following Transepithelial Photorefractive Keratectomy in Myopic Patients

Abstract: This study investigated the effect of prophylactic mitomycin C (MMC) on corneal endothelium to inhibit corneal haze formation post transepithelial photorefractive keratectomy (T-PRK). Methods: A total of 120 eyes of 60 patients with low, moderate, and high myopia were subjected to T-PRK with intraoperative application of MMC (0.02%) for 30-50s. Patients' files were categorized into three groups according to ablation depths (if ≥100 µm) during T-PRK as follows: (1) Group A -low myopia without MMC, (2) Group B -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In addition, an intraoperative application of MMC 0.02% for 30 s caused no significant change in ECD. A recent study by Al-Mohaimeed et al [ 71 ] also revealed the safety and efficacy of the use of MMC in reducing corneal haze after Trans-PRK in low to high order myopia. MMC exerted no effect on the number or density of corneal endothelial cells.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, an intraoperative application of MMC 0.02% for 30 s caused no significant change in ECD. A recent study by Al-Mohaimeed et al [ 71 ] also revealed the safety and efficacy of the use of MMC in reducing corneal haze after Trans-PRK in low to high order myopia. MMC exerted no effect on the number or density of corneal endothelial cells.…”
Section: Discussionmentioning
confidence: 95%
“…During the procedure, multiple slit lamp examinations of the cornea may be necessary until the surgeon feels comfortable that they have removed enough of the scar. Afterwards, a sponge can be used to apply 0.02% MMC to the surface for 2 min [ 5 , 7 , 53 , 72 ], following which the cornea will be irrigated continuously with 20–30 cc of cold or room temperature saline solution. The application of MMC and the appropriate concentration are still controversial topics, especially for low myopia eyes [ 96 ], due to MMC-related tissue toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the authors of this study did not disclose the specific duration for each ablation depth . A much smaller study carried out in 2022 included 120 eyes that underwent t-PRK and then treated with 0.02% MMC for 30–50 s without specification of ablation depth [ 72 ]. In this study, one eye developed post PRK haze [ 72 ].…”
Section: Prk Haze Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its effectiveness in preserving corneal transparency and preventing the formation of opacity, it is currently used as a preventive agent for haze following high-risk PRK [7][8] . Several studies have demonstrated the potential of MMC in suppressing haze formation, but its application is also risky [9] . Research findings suggest that MMC may exert an impact on the cellularity of the anterior stroma, corneal nerves, and corneal endothelium.…”
Section: Dear Editormentioning
confidence: 99%